Synthesis and characterization of benzyl and benzoyl substituted oxime-phosphazenes - Cil, E.; Arslan, M.; Gorgulu, A. O. (Pergamon-Elsevier Science Ltd, 2006)
Two oxime-cyclophosphazenes were prepared from hexakis(4-formylphenoxy)cyclotriphosphazene (2) and hexakis(4-acetylphenoxy)cyclotriphosphazene (7). The reactions of these oximes with benzyl chloride, benzenesulfanoyl chloride, benzoyl chloride, 4-methoxybenzoyl chloride and 2-chlorobenzoyl chloride were studied. Hexa and pentasubstituted compounds were obtained from the reaction of hexakis(4-[(hydroxyimino)methyl]phenoxy)cyclotriphosphazene (3) with benzyl chloride (4) and benzoyl chloride, respectively. However, the oxime groups on 3 rearranged to nitrile (5) in the reaction of 3 with benzenesulfanoyl chloride and 1-napthalenesulfanoyl chloride. Hexasubstituted compounds were also obtained from the reactions of hexakis(4-[(1)-N-hydroxyethaneimidoyl]phenoxy)cyclotriphosphazene (8) with benzoyl chloride (10), 4-methoxybenzoyl chloride (11) and 2-chlorobenzoyl chloride (12). A trisubstituted compound was obtained from the reaction of 8 with benzyl chloride (9). All the products were generally obtained in high yields. Pure and defined products could not be obtained from the reaction of 3 with 4-methoxybenzoyl chloride and 2-chlorobenzoyl chloride. The structures of the compounds were defined by elemental analysis, IR, H-1, C-13 and P-31 NMR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: hexachlorocyclotriphosphazene; phosphazene; oxime; oxime derivatives; oxime-phosphazenes